Calcipotriol/betamethasone foam for proactive management of plaque psoriasis: four case reports - Zoe Apalla; Marc Perrussel; Efstathios Rallis (BioExcel Publishing Ltd, 2022)
Psoriasis is a chronic inflammatory disease affecting about 100 million people worldwide. Around 80% of patients can be treated with topical agents, most commonly corticosteroids and vitamin D analogues. A topical foam formulation of calcipotriol (50 μg/g) and betamethasone dipropionate (0.5 mg/g) (Cal/BD foam; Enstilar®) is approved for the daily treatment of psoriasis for up to 4 weeks and twice-weekly thereafter as maintenance treatment (after initial 4-week treatment success). Long-term proactive maintenance with Cal/BD foam for plaque psoriasis has been shown to prolong the time to first relapse, reduce the number of relapses and increase days in remission in the PSO-LONG trial. Four case studies of proactive management with Cal/BD foam for the treatment of plaque psoriasis for up to 12 months from initial presentation are described. These case studies provide real-world evidence on the long-term effectiveness of proactive management with Cal/BD foam as well as the improvement and maintenance of health-related quality of life. Cal/BD foam was well tolerated.